2010
DOI: 10.1007/s10479-010-0706-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic pricing and inventory control: robust vs. stochastic uncertainty models—a computational study

Abstract: In this paper, we consider a variety of models for dealing with demand uncertainty for a joint dynamic pricing and inventory control problem in a make-to-stock manufacturing system. We consider a multi-product capacitated, dynamic setting, where demand depends linearly on the price. Our goal is to address demand uncertainty using various robust and stochastic optimization approaches. For each of these approaches, we first introduce closed-loop formulations (adjustable robust and dynamic programming), where dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…utilized factor-based models in constructing uncertainty sets [22,11,10]. An alternate, and possibly less conservative, data-driven model of such a problem that employs a point estimate of the mean and covariance matrix requires the solution of two coupled problems: (1) A portfolio optimization problem parametrized by (θ * , Σ * ) representing the mean and covariance matrix of returns; and (2) A learning problem that utilizes data to obtain the best (θ * , Σ * ).…”
mentioning
confidence: 99%
“…utilized factor-based models in constructing uncertainty sets [22,11,10]. An alternate, and possibly less conservative, data-driven model of such a problem that employs a point estimate of the mean and covariance matrix requires the solution of two coupled problems: (1) A portfolio optimization problem parametrized by (θ * , Σ * ) representing the mean and covariance matrix of returns; and (2) A learning problem that utilizes data to obtain the best (θ * , Σ * ).…”
mentioning
confidence: 99%
“…These authors assume that there is no demand noise, which means that the unknown parameters that determine the demand function are completely known once a demand realization is observed that does not lead to stock-out. Adida and Perakis (2010a) discuss several robust and stochastic optimization approaches to joint pricing and procurement under demand uncertainty, and compare these approaches with each other in a numerical study.…”
Section: Joint Pricing and Inventory Problemsmentioning
confidence: 99%
“…For instance, we can construct a budget of uncertainty across products, for a given parameter and at a given time, as suggested in Adida and Perakis [2]:…”
Section: Uncertainty In Demand Parametersmentioning
confidence: 99%